Timeless teachers and ethical visions : human development and educational policy - Kuriakose, K. K. (Emerald Publishing Limited : Information Age Publishing, 2013)
The industrial monoculture spreading across the globe is highly competitive, greedy and egotistical; in the shaping of educational policy, global communities have accepted a model based on science and technology, which lacks aspects that should be addressed in the goal of education. The book Timeless Teachers and Ethical Visions is a historical inquiry of educational concerns that have developed through the centuries. It is a systematic discussion of prominent educators, including their theories and experiments: St. Thomas Aquinas, Al-Ghazali, Ibn Khaldun, Leo Tolstoy, Mahatma Gandhi, John Dewey and Paulo Freire.In addition, the inquiry investigates the strengths and weaknesses of the neoliberal educational policy, the suggestions to construct an educational policy considering the common good, criticize uncontrolled individualism while emphasizing the goal of education that enhances community consciousness to the learner. Finally, the aim of this book is to propose an alternative educational policy that is beneficial to the global community.
Keywords: Education -- Philosophy.; Globalization.; Education and state.; Education -- Educational Policy & Reform -- General.; Moral and social purpose of education.; Educational strategies and policy.; elektronické knihy; electronic books